Rancang Bangun Sistem Terapi Infrared Otomatis Untuk Terapi Far-Infrared Pada Spinal Cord - Eko Arianto; Bernardinus Sri Widodo (Politeknik Aceh, 2022)
Infrared therapy is a therapy that is mostly done by utilizing the effects of heat generated on the human body, especially on the surface of the skin that is directly exposed. There are several types of infrared but the most commonly used for therapy is far-infrared (FIR). The dose of infrared therapy varies with a range of 10-45 minutes and is carried out several times a week. In Indonesia, most infrared therapy uses a portable infrared lamp. In infrared therapy, there are several things that must be done, such as keeping the infrared lamp distance from the patient's body, maintaining therapy time, and adjust position to the location that needs therapy. There are three parameters that must always be monitored and controlled: distance, time, and position. To adjust these three parameters with a fairly long duration of therapy, it is quite tiring for the therapist or people who help the therapy. With these problems, an automatic infrared therapy system will be very helpful. The design of the automatic infrared therapy system can help solve existing problems such as being able to control the timer, distance, and position of infrared therapy. The infrared therapy system that has been successfully created can work well. The proximity sensor works accurately, the motion mechanism and the timer also work well. Keywords: automatic infrared therapy, automatic therapy, infrared therapy, FIR therapy